2017
DOI: 10.1097/yco.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychopathology in children of parents with mental illness and/or addiction

Abstract: This knowledge should encourage mental health services to address the needs of these children which requires strong collaboration between Child and Adolescent Mental Health Services and Adult Mental Health Services. Directions for further research would be to include both parents, allow for comorbidity and to look deeper into a broader variety of mental illnesses such as autism and personality disorder other than borderline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 51 publications
5
91
1
9
Order By: Relevance
“…Factors that contribute to this phenomenon continue to be identified and discussed. One such factor is the possible impact of parental mental illness on children (Leijdesdorff et al ), a circumstance estimated to affect 50% of children. Furthermore, Maybery and Reupert () suggest that 20.4 to 38.5% of adult consumers of public mental health services are parents.…”
Section: Overviewmentioning
confidence: 99%
“…Factors that contribute to this phenomenon continue to be identified and discussed. One such factor is the possible impact of parental mental illness on children (Leijdesdorff et al ), a circumstance estimated to affect 50% of children. Furthermore, Maybery and Reupert () suggest that 20.4 to 38.5% of adult consumers of public mental health services are parents.…”
Section: Overviewmentioning
confidence: 99%
“…26,27 Similar to international trends, there has been an increased focus on the needs of children with parents with mental health problems. [12][13][14][15][16][17][18] Consequently, in 2010, Norway added two legislative provisions that oblige health personnel to attend to minor relatives and to designate children-responsible staff (CRS). 28,29 The responsibilities of CRS are to promote and coordinate health personnel's follow-up with patients' minor children.…”
Section: Study Contextmentioning
confidence: 99%
“…5,11 Studies have clearly shown that the children of parents with serious mental health problems face many developmental, emotional, behavioural and educational challenges and are at risk of developing mental health problems themselves. [12][13][14][15][16] Therefore, health personnel should ascertain what kind of support measures these children need and start the necessary followup. [17][18] In Norway, about 15-20% of all hospitalised patients are involuntarily admitted (about 5000 adults).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that between 15% and 23% of children globally, and at least 23.3% of Australian children, live with a parent with mental illness (Maybery, Reupert, Patrick, Goodyear, & Crase, ; Leijdesdorff, van Doesum, Popma, Klaassen, & van Amelsvoort, ). Although there has been substantial research on this target group, more research efforts are needed to explore the long‐term impact of parental mental illness on adult children (Foster, ).…”
Section: Introductionmentioning
confidence: 99%